Concurrent Rabies and Canine Distemper Outbreaks and Infection in Endangered Ethiopian Wolves - Jorgelina Marino; Elizabeth F.R. Preston; Muktar Abute; Alo Hussein; Fekede Regassa; Asefa Deressa; Eric Bedin; Ashley C. Banyard; Anthony R. Fooks; Claudio Sillero-Zubiri (Emerging Infectious Diseases)
Intensive disease surveillance in an endangered population of Ethiopian wolves provided evidence of concurrent outbreaks of rabies and canine distemper viruses in 2019, including co-infection in an individual animal. Disease surveillance and intensive monitoring of wolf packs in Ethiopia were essential in detecting the concurrent outbreaks and enabled accurate assessment of disease from both pathogens. The study highlights the risk posed to endangered populations that are susceptible to, or live in areas with, reservoir hosts for canine distemper and rabies viruses. Instances of concurrent distemper and rabies outbreaks appear unusual in the existing literature; modeling for one disease might underestimate the risk for extinction. Concurrent outbreaks may have a larger effect than single-disease outbreaks, even in a population that has partial vaccination coverage. Researchers studying wildlife populations from a conservation perspective should be aware that both diseases can strike at once where susceptible populations exist.